DEVELOPING CAPACITY BUILDING SMEs IN WEST JAVA - Suhardi, Dadang (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Small and Medium Enterprises (SMEs) are the business groups that are most able to survive in the event of an economic crisis. The development of the number of small and medium business units that continues to increase, this will certainly open up large employment opportunities so that the number of unemployed people decreases. The presence of SMEs in terms of managerial level and ability is still low, there are still a few of our SME entrepreneurs with Bachelor degrees. The fact shows that the quality of SMEs resources is still low, especially in the fields of management, organization, mastery of technology and marketing. The low level of education of small and medium entrepreneurs was apparently not matched by capacity building efforts through training, education and programmatic comparative studies. HR has an important role in achieving success, because sophisticated and complete facilities are not yet a guarantee of the success of an organization without being balanced by the quality of human resources who will utilize the facility. This study seeks to examine strategies that can be used by SMEs in an effort to improve HR capacity by covering the determination of samples using purposive sampling method, which then data is analyzed using multiple linear regression an